How Can we Use Simulation to Improve Competencies in Nursing? (Springer Nature, 2022)
This open access book offers an overview of theories related to simulation and describes different simulation areas within nursing. It illustrates how simulation may be used in different levels in professional education. The book deals with the role of the Simulation Facilitator, peer learning and the use of Virtual Reality in simulation. It provides new insights and paths to the development of the use of simulation within nursing and healthcare and contributes with new knowledge from research and experiences of implementation of different simulating scenarios within nursing and midwifery. It is intended to teachers in nursing and other healthcare professionals with an interest in the use of active learning methods.